Study on harmonic analysis of functionally graded plates using FEM - Sharma, Avadesh Kumar; Chauhan, Premanand Singh; Sharma, P.; Bhadoria, Shailendra Singh (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the harmonic and vibration analysis of functionally graded plates using the finite element method. Initially, the plates are assumed isotropic and the material properties of it are assumed to vary continuously through their thickness direction according to a power-law distribution of the volume fractions of the plate constituents. The four noded shell element is used to analyse the functionally graded plates.
Keywords: Finite Element Method (FEM); functionally graded plates; free vibrations